2011
DOI: 10.1007/s10811-011-9700-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased CO2 levels on growth, photosynthesis, ammonium uptake and cell composition in the macroalga Hypnea spinella (Gigartinales, Rhodophyta)

Abstract: The red seaweed Hypnea spinella (Gigartinales, Rhodophyta), was cultured at laboratory scale under three different CO 2 conditions, non-enriched air (360 ppm CO 2 ) and CO 2 -enriched air at two final concentrations (750 and 1,600 ppm CO 2 ), in order to evaluate the influence of increased CO 2 concentrations on growth, photosynthetic capacity, nitrogen removal efficiency, and chemical cellular composition. Average specific growth rates of H. spinella treated with 750 and 1,600 ppm CO 2 -enriched air increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 51 publications
5
9
0
Order By: Relevance
“…The same has been reported for Hizikia fusiforme (currently, Sargassum fusiforme), Hypnea spinella, and Pyropia haitanensis (Zou 2005;Suárez-Álvarez et al 2012;Chen et al 2016). Zou et al (2004) showed that the photosynthesis of G. lemaneiformis is already saturated under normal DIC concentrations found in natural seawater.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The same has been reported for Hizikia fusiforme (currently, Sargassum fusiforme), Hypnea spinella, and Pyropia haitanensis (Zou 2005;Suárez-Álvarez et al 2012;Chen et al 2016). Zou et al (2004) showed that the photosynthesis of G. lemaneiformis is already saturated under normal DIC concentrations found in natural seawater.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have revealed similar results with G. lemaneiformis, Hypnea spinella, Chondrus crispus, Pyropia haitanensis, and Ulva pertusa (Yu and Yang 2008;Suárez-Álvarez et al 2012;Sarker et al 2013;Chen et al 2016;Kang and Chung 2017). When DIC concentrations rise in the ocean, many macroalgal species conserve energy by regulating their CCMs, thereby improving their growth performance (Sarker et al 2013).…”
Section: Discussionmentioning
confidence: 54%
“…The fact that this is the first time that a kelp-specific extraction method is used rendering high efficiency explains why the protein content from both temperate and Arctic S. latissima (Fig. 1) was higher than those reported for most other brown algae except Undaria pinnatifida (Fleurence 1999; Hernández-Carmona et al 2009; Westermeier et al 2012), and similar to values obtained in the red alga Hypnea spinella (Suárez-Álvarez et al 2012). …”
Section: Discussionsupporting
confidence: 70%
“…In this sense, Olabarria et al (2012) showed that the N-content of the red, respectively, brown seaweed Chondrus crispus and Cystoseira tamariscifolia were positively affected by an increase in pCO 2 , while the red alga Mastocarpus stellatus and the brown seaweeds Sargassum muticum were not affected. On the other hand, the red alga Hypnea spinella responded in a similar way than HL-population at 10 °C, increasing C/N-ratio at elevated pCO 2 conditions, while C-content remain constant (Suárez-Álvarez et al 2012). Experimental studies have shown that responses of internal N-content to CO 2 enrichment vary greatly between different algae (Gordillo et al 1999; Andría et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence of a decrease in respiration rate by high CO 2 concentrations has been reported in vascular plants (Bunce and Caulfield 1991;Azcón-Bieto et al 1994) and in the chlorophyte Ulva rigida (Gordillo et al 2001), in the latter allowing an increase in growth rate despite the unchanged photosynthetic rate, while other macroalgal species did not change their respiration rate when exposed to increased CO 2 (Zou and Gao 2009;Zou et al 2011a;Suárez-Á lvarez et al 2012).…”
Section: Introductionmentioning
confidence: 75%